Cardiomyocyte uptake mechanism of a hydroxyapatite nanoparticle mediated gene delivery system - Komuro, Hiroaki; Yamazoe, Masahiro; Nozaki, Kosuke; Nagai, Akiko; Sasano, Tetsuo (Beilstein Journal of Nanotechnology, 2020)
Gene therapy has been explored as a future alternative for treating heart disease. Among several gene delivery systems aimed at penetrating specific target cells, we focused on safe and non-viral gene delivery materials with a high transfection efficiency. Although various techniques have been developed, the mechanisms underlying the cellular uptake of gene delivery materials have not yet been sufficiently studied in cardiomyocytes. The aim of this study was to determine how hydroxyapatite (HAp) nanoparticles contribute to the delivery of plasmid DNA (pDNA) into cardiomyocytes. We fabricated HAp nanoparticles using the water-in-oil (W/O) emulsion method and used these nanoparticles as the delivery vector for transfecting cardiomyocyte-derived HL-1 cells. HAp exhibited particles on the nanoscale and with a low cytotoxicity in HL-1 cells. The transfection assay performed with several endocytosis inhibitors suggested that the HAp/pDNA complexes were internalized by HL-1 cells through macropinocytosis. Furthermore, this HL-1 cell uptake was generated in response to HAp stimulation. Thus, HAp is a positive regulator of macropinocytosis in HL-1 cells and a good system for gene delivery in cardiomyocytes.
Keywords: cardiomyocyte; endocytosis; gene delivery system; hydroxyapatite nanoparticles; macropinocytosis